Critical appraisal of the documentation about Tudela’s Christian conquest - Hernández Charro, María Carmen (Huarte de San Juan. Geografía e Historia, 2011)
This paper is focused on the Tudela’s Christian conquest and the subsequent transformation undergone by Tudela after the arrival of the Christian rulers. This event meant a territorial expansion and a social change. Most of the article is orientated to do a revision of the documents where are based the researches of historians like José María Lacarra, which dates are supposed to be incorrect. Consequently, it is tried to study the possibility of the truthfulness of the dates in these documents. With this review is not tried to refute the previous researches made by Jose María Lacarra, but understand the politic, economic and social situation that Tudela lived during the 11th century and the early 12th century when it was conquest by Alfonso I the Battler. To do that, some important events are studied like the early conquest of Arguedas (1084), Valtierra’s battle in 1110 and the aid of the French and Norman knights before 1119.